(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Newborn Screening is a screening program that helps to detect common and treatable or preventable congenital metabolic-endocrine and genetic disorders in newborn babies. Detected through a screening test kit for 5 diseases: G6PD deficiency, congenital hypothyroidism, congenital adrenal hyperplasia, Galactosemia, Phenylketonuria Objectives: Determine the rate of newborns at high risk of 5 diseases and the relationship with epidemiological factors. Methods: Using cross-sectional descriptive method for newborns full 24-72 hours old born at Nghe An Obstetrics and Pediatrics Hospital from January 2022 to June 2022. Results: Through surveying 3147 samples of heel in newborns, we found that the abnormal rate of newborn screening tests accounted for the following: G6PD deficiency accounted for 0,86%, of which, male accounted for 70,37%, girls account for 29.63%. Congenital hypothyroidism is 0.22%. Congenital adrenal hyperplasia is 0,13%. Phenylketonuria was 0,1% and none of the children were in the high-risk group for galactosemia. Conclusions: 5 newborn screening diseases, if detected early, can be prevented and treated so that children can have a completely healthy life. Therefore, it is necessary to strengthen screening counseling to improve population quality and improve living standards.